P013 APOPTOTIC ENTEROPATHY INDUCED BY THALIDOMIDE IN A PATIENT WITH REFRACTORY UPPER AND COLONIC CROHNS' DISEASE. (18th January 2018) - Donet, Jean A; Garcia-Buitrago, Monica; Sedki, Mai; Diaz, Liege; Cohen, David; Kerman, David
Abstract: Apoptotic bodies can be found to be marginally increased in untreated IBD. However, the presence of more than 6 apoptotic bodies per 10 contiguous crypts warrants further investigation. Apoptotic enteropathy (AE) has been described in different conditions including Graft–versus–Host disease (GVHD), idiopathic AIDS enteropathy, chronic variable immunodeficiency, autoimmune enterocolitis, and viral infections. AE has also been reported as a side effect of various medications including: NSAIDS, Mycophenolic acid, 5–Fluorouracil, Ipilimumab, Capecitabine, Etanercept as well as inflammatory bowel disease (IBD) drugs-Methotrexate (MTX), Infliximab, and Adalimumab (ADA). We report a complex case of a patient with refractory upper and colonic Crohn's disease (CD) who developed histologic changes consistent with AE one year after starting thalidomide for management of her IBD. The proposed mechanism for thalidomide-induced AE is thought to be mediated by the cytochrome c-dependent apoptotic pathway which leads to caspase activation in turn leading to apoptosis. To the best of our knowledge, this is the first report relating thalidomide to AE. Thalidomide should be considered in the differential diagnosis in patients with AE. IBD specialists, gastroenterologists and pathologists should be aware of the expanding spectrum of drugs that can cause AE, including thalidomide among others.